Examining the Media Coverage of the 2024 Indonesian Presidential Election on Tempo.co's Online Platforms - Yusmanizar, Yusmanizar; Mahdar, Mahdar; Syahruddin, Syahruddin; Menungsa, Abdul Sarlan; Alim, Nur (Institut Agama Islam Negeri Kendari, 2024)
This article discusses the analysis of news content about conditions after the 2024 Presidential and Vice Presidential Elections. Researchers will analyze six news reported by Tempo.co online media between February 15 and 18, 2024. The news is analyzed to find out how journalism works and construct reality carried out by Tempo.co. The media, which is business-under the auspices of the Tempo Media Group company, has been known to be independent and critical. This research uses Holsti Theory or (Holsti Theory) to analyze the content of Tempo.co news with descriptive analysis methods. The subject of this study is Tempo.co as a source of information researchers get data. The object of research is six post-2024 Presidential Election news on the Tempo.co page of the February 15-18, 2024 edition. Supporting sources for this research are books and other research journals that can explain the information needed by researchers. The results showed that Tempo.co reported the dynamics of the 2024 Presidential Election within the framework of critical, analytical, and independent journalism, but still prioritized the principle of balancing or covering both sides, verified, and factual (based on facts). Tempo.co presents news about the presidential election without having a tendency of interest and only presents facts with the selection of competent sources. This is evidenced by the variation of post-Presidential Election news without cornering any of the three existing Presidential Candidate-Vice President pairs. Keywords: Content Analysis; Journalism; Presidential Election; Tempo.co